2014
DOI: 10.4149/gpb_2013059
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency magnetic fields induce oxidative stress in rat brain

Abstract: Abstract. The present investigation was conducted to understand the influence of long-term exposure of rats to extremely low frequency magnetic fields (ELF-MF), focusing on oxidative stress (OS) on different regions of rat's brain. Male Wistar rats (21-day-old) were exposed to ELF-MF (50 Hz; 50 and 100 µT) for 90 days continuously; hippocampal, cerebellar and cortical regions from rats were analyzed for (i) reactive oxygen species (ROS), (ii) metabolites indicative of OS and (iii) antioxidant enzymes. In compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…For example, Calcabrini and his colleagues observed that 0.05/0.1 mT 50 Hz exposure for 1/2 h could increase ROS level in human keratinocyte cell line (NCTC 2544), but return to normal level at 4 h, while a lower intensity (0.025 mT) or a higher intensity (0.15/0.2 mT) did not cause ROS changes [ 59 ]. In addition, Manikonda showed that EMF-induced ROS level changes in rat brain are tissue- and intensity-specific [ 85 ]. Moreover, ELF-EMFs frequency is also important [ 66 , 67 ].…”
Section: The Effects Of Magnetic Fields On Rosmentioning
confidence: 99%
“…For example, Calcabrini and his colleagues observed that 0.05/0.1 mT 50 Hz exposure for 1/2 h could increase ROS level in human keratinocyte cell line (NCTC 2544), but return to normal level at 4 h, while a lower intensity (0.025 mT) or a higher intensity (0.15/0.2 mT) did not cause ROS changes [ 59 ]. In addition, Manikonda showed that EMF-induced ROS level changes in rat brain are tissue- and intensity-specific [ 85 ]. Moreover, ELF-EMFs frequency is also important [ 66 , 67 ].…”
Section: The Effects Of Magnetic Fields On Rosmentioning
confidence: 99%
“…Recent research on the effects of electromagnetic fields on animal (rat) cells and on human cells is of great interest [ 5 , 22 ]. However, there are only a few inconclusive published papers and limited data available on the effects of ELF-MFs on the level of serotonin and its metabolite concentrations in animals.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that depression is an illness that diminishes the quality of people's life around the world [ 1 , 2 ]. In the past two decades, considerable evidence has come to light indicating that changes in serotonergic function in the central nervous system of patients causes acute depression [ 3 5 ]. In other evidence, extremely low frequency magnetic fields (ELF-MFs) have been shown to influence the nervous and neurotransmitter systems in the brain [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…All studies have agreed that the deleterious effects of EMF exposure on living organisms depend on the frequency and density of the field and the time of exposure. Some authors have concluded that genotoxicity after exposure to EMF is secondary to other mechanisms, such as the production of free radicals [9][10][11].…”
Section: Introductionmentioning
confidence: 99%